Fire safety practices among residents in Azelia Bukit Banyan, Sungai Petani, Kedah - Lai, Pauline Huey Min (2017)
Residential fire is one of the fire incidents that significantly contribute to fire casualties nationwide. Human errors are common factor which lead to residential fires. The extent of residents committed to home fire safety practically and theoretically is determined through the study of home fire safety practices among residents within the selected residential area. In this study, 170 of respondents in Azelia Bukit Banyan are selected to answer the questionnaire provided. The main objective of this study is accomplished through fire hazard identification as well as fire safety awareness and knowledge evaluation process among the studied group involving residents at Bukit Bayan, Sungai Petani, Kedah. Home Fire Safety (HFS) Checklist is used to identify type of fire hazards existed at the house which create risk to fire incident at home. On the other hand, a self-administered Home Fire Safety Questionnaire were developed and distributed to the selected respondents which examine and evaluate the level of awareness and knowledge regarding to fire safety at home among residents. Data collected from questionnaire were analysed by a descriptive data analysis software called Statistical Package for Social Science (SPSS). Secondary statistical analysis by simple percentage conversion is carried out to analyse the information from HFS Checklist. Results of this study showed various type of fire hazards identified in the residential building. Besides that, the level of awareness and knowledge regarding to home fire safety practices among residents are moderately acceptable. Information can be extracted from the result of findings in order to establish further actions in fire safety practices among residents.